Investigating the Effects of Salinomycin on Interleukin Receptor Gene Expression Levels in Acute Myeloid Leukemia Cells - Muslim Mohammed Mosa Jassim; Ali Khairi Hadi Altameemi; Haider Ali Abdzaid; Yaseen Musafer Abed; Hussein M. M. Jaafar (Journal of Applied Hematology)
BACKGROUND: Acute myeloid leukemia (AML) is heterogeneous aggressive hematological cancer marked by rapid proliferation of abnormal myeloid cells. Salinomycin (SAL), traditionally used as an anticoccidial drug, has recently been shown to possess anticancer and anticancer stem cell effects. OBJECTIVE: To elucidate the potential anticancer effects of SAL against KG-1a cell lines. MATERIALS AND METHODS: KG-1a cells were grown in Roswell Park Memorial Institute (medium) 1640 medium and given different amounts of SAL for 24–72 h. The harmful effects on cells were tested using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method, and changes in cell shape were checked with Hoechst spotting. We studied how SAL affects interleukin-6 receptor (IL-6R) gene expression using real-time quantitative polymerase chain reaction, and we compared the results to beta-actin. Statistical analysis with t-tests and analysis of variance were performed, and results were considered significant if the P < 0.05. RESULTS: The results demonstrated that SAL had significant cytotoxic effects on KG-1a cells at various concentrations. Assessment of cell viability at different time points (24, 48, and 72 h) revealed a notable decrease in cell viability as the concentration of SAL and incubation time increased. The results showed significant changes in the nuclear structure of the treated cells, indicative of apoptosis initiation. Treatment with SAL resulted in a significant downregulation (P < 0.0001) of IL-6R mRNA levels. CONCLUSION: These findings suggest that SAL acts as a potent antileukemic agent with significant cytotoxic effects on AML cells and downregulates key genes involved in cellular signaling pathways.